Xanthogranulomatous pyelonephritis presenting as palmoplantar keratoderma. - Caetano, J (2016)
Submitted by arminda sustelo (arminda.sustelo@hff.min-saude.pt) on 2016-11-15T15:07:59Z No. of bitstreams: 1 BMJ Case Rep. 2014 Dec 17.pdf: 1031033 bytes, checksum: 8a970887adc51ddd442e71cb1ea5d404 (MD5)